Grassland bird nest ecology and survival in upland habitat buffers near wooded edges - Ross R. Conover; L. Wes Burger Jr.; Eric T. Linder (Wildlife Society Bulletin)
Abstract Upland habitat buffers (i.e., strips of noncrop, herbaceous vegetation) that are established adjacent to wooded fencerows offer landowners an economical option to provide wildlife benefits within intensive agricultural landscapes. However, being located near a wooded edge may increase grassland bird vulnerability to edge effects through reduced nest survival. We examined nesting bird communities in field margins adjacent to wooded field edges with no buffer (i.e., control), narrow (approx. 10‐m) buffers, and wide (approx. 30‐m) buffers in an intensive agricultural system in the Lower Mississippi Alluvial Valley, United States. Dickcissel (Spiza americana) and red‐winged blackbird (Agelaius phoeniceus) accounted for 97% of nests. Nest density was >7 times greater in wide buffers than in narrow. We modeled nest survival in Program MARK as a function of time (yr and season), nest‐site, and local vegetation characteristics. Nest survival was influenced by among‐ and within‐season temporal effects and local vegetation structure, but not by buffer width. Nest success varied substantially between years and within seasons for dickcissel (12.9% and 19.1% early in the seasons of 2003 and 2004, respectively), but not for red‐winged blackbird (15.1%). Overall nest‐success estimates were similar to noncrop, herbaceous strips elsewhere in the United States, though whether or not these estimates represent population sinks remains uncertain. Based on this research, we advocate integrating upland habitat buffers within intensive agricultural landscapes and emphasize the use of wide buffers when grassland‐nesting birds are a conservation priority. © 2011 The Wildlife Society.